PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA PEMBELAJARAN IPA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS VIII E DI SMP N 12 KOTA BENGKULU - MELLY NORITA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to determine the results of the Application of the Discovery Learning Learning Model in Science Learning to Increase the Activities and Learning Outcomes of Class VIII E Students at SMP N 12 Bengkulu City. The type of research used is Classroom Action Research (CAR), which is carried out in 2 cycles. The research subjects to be studied were all students in class VIII E semester II of SMP Negeri 12 Bengkulu City for the 2021/2022 academic year as many as 38 students consisting of 17 boys and 21 girls. Place of research at SMPN 12 Bengkulu City. This research was carried out in September 2021. The CAR procedure consists of four basic stages that are interrelated and continuous, namely planning, implementing, observing and reflecting. There are 2 instruments used in this research, namely the observation sheet and the test sheet. The results of the study show that: 1) The application of discovery learning learning models can increase learning activities. This can be seen from the increase in the average student activity score in cycle I with an average of 45 with sufficient criteria increasing to 65.5 in cycle II with good criteria. 2) Application of the discovery learning learning model can improve student learning outcomes in science subjects class VIII E SMPN 12 Bengkulu City. The average final score of students in the first cycle was 72.76 and the learning completeness reached 55.26% (incomplete) increased in the second cycle the average final score of students was 80.52 and the learning completeness was 89.47% (complete). ABSTRAKPenelitian ini bertujuan untuk mengetahui hasil Penerapan Model Pembelajaran Discovery Learning Pada Pembelajaran IPA untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Kelas VIII E di SMP N 12 Kota Bengkulu. Jenis penelitian yang digunakan adalah Penilitian Tindakan Kelas (PTK), yang dilaksanakan dalam 2 siklus. Subjek Penelitian yang akan diteliti adalah seluruh siswa kelas VIII E semester II SMP Negeri 12 Kota Bengkulu tahun pelajaran 2021/2022 sebanyak 38 siswa yang terdiri dari 17 orang laki-laki dan 21 orang perempuan. Tempat penelitian di SMPN 12 Kota Bengkulu. Penelitian ini dilaksanakan pada bulan September 2021. Prosedur PTK terdiri dari empat tahapan dasar yang saling terkait dan berkesinambungan yaitu perencanaan, pelaksanaan, pengamatan dan refleksi. Instrumen yang digunakan dalam penelelitian ini ada 2, yaitu lembar observasi dan lembar tes. Hasil penelitian menunjukkan bahwa: 1) Penerapan model pembelajaran discovery learning dapat meningkatkan aktivitas pembelajaran. Hal ini terlihat dari peningkatan rata-rata skor aktivitas siswa pada siklus I dengan rata-rata 45 dengan kriteria cukup meningkat menjadi 65,5 pada siklus II dengan kriteria baik. 2) Penerapan model pembelajaran discovery learning dapat meningkatkan hasil belajar siswa pada mata pelajaran IPA kelas VIII E SMPN 12 Kota Bengkulu. Rata-rata nilai akhir siswa pada siklus I 72,76 dan ketuntasan belajar mencapai 55,26 % (belum tuntas) meningkat pada siklus II rata-rata nilai akhir siswa 80,52 dan ketuntasan belajar 89,47 % (tuntas).